On the spectrum of facet crystallization waves at the smooth 4He crystal surface - Burmistrov, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The wavelike processes of crystallization and melting or crystallization waves are well known to exist at the 4He crystal surface in the rough state. Much less is known about crystallization waves for the 4He crystal surface in the smooth well-faceted state below the roughening transition temperature. To meet the lack, we analyze here the spectrum of facet crystallization waves and its dependence upon the wavelength, perturbation amplitude, and the number of possible facet steps distributed somehow over the wavelength. All the distinctive features of facet crystallization waves from conventional waves at the rough surface result from a nonanalytic cusplike behavior in the angle dependence for the surface tension of smooth crystal facets.